Statins, atherosclerosis regression and HDL: Insights from within the plaque. (15th June 2015) - Feig, Jonathan E.; Feig, Jessica L.; Kini, Annapoorna S.
Abstract: The idea that atheroma can regress is no longer a dream. We and others have discovered that decreasing the lipid content can directly lead to macrophage egress and plaque healing. The question, however, has remained as to how to translate these findings to the bedside. Taking advantage of imaging modalities such as intravascular ultrasound (IVUS) and near infrared spectroscopy (NIRS), we demonstrated in the YELLOW (Reduction in Yellow Plaque by Intensive Lipid Lowering Therapy) trial that short term treatment of high dose rosuvastatin treatment can lead to a decrease in lipid content in plaques. It is important to note that optical coherence tomography (OCT), a high resolution imaging modality, was not performed during the first study and therefore, only a very limited assessment of the effect of statin therapy on measures of plaque stabilization could be made. The YELLOW II trial is the first to our knowledge to determine whether these data can be extrapolated and how it relates to HDL function, alterations in macrophage gene expression, and plaque morphology. While tremendous progress has been made, our research serves as a reminder that angiography is simply luminography and it is features such as thin cap fibroatheroma and lipid burden, for example, that likely modulate the syndromes seen in clinical practice. Ongoing studies such as ours may provide novel pathways for diagnosis and therapy, with the ultimate goal of reducing the burden of cardiovascular disease.